The Correlation Between Students’ Learning Motivation and Reading Comprehension at the Tenth Grade of SMA Kemala Bhayangkari North Lampung in Academic Year 2020/2021 - Icha, Janisa Ramadasari (Griya Cendikia, 2022)
Abstract: The researcher conducted a study with the aim of knowing whether there was a significant correlation between students’ learning motivation and reading comprehension at the tenth grade of SMA Kemala Bhayangkari North Lampung in academic year 2020/2021. The type of research used in quantitative research with the method of correlation technique The research population was all students of class X, totaling 111 students. While the sample was taken using a simple random sampling technique with a total of 25 students. Data collection techniques obtained from research on learning motivation as an independent variable (X), in the form of a questionnaire to obtain information from respondents, while reading comprehension is the dependent variable (Y), in the form of multiple choice test to determine aspects in assessment reading and measure of students’ ability in reading comprehension. Then from these results a normality test was carried out using the Lilliefors test and then a homogeneity test was carried out using the F test, and hypothesis testing. The results of hypothesis testing based on data analysis resulted in a correlation coefficient (rxy ) of 0,806 (rcount = 0,806 > rtable = 0,396 ).